Hydroponic food production : a definitive guidebook for the advanced home gardener and the commercial hydroponic grower - Resh, Howard M. (Boca Raton, FL : CRC Press, 2013)
Reviews the history of hydroponics, the growing of plants without soil, and offers guidance for home gardeners and commercial hydroponic growers on plant nutrition; the nutrient solution; nutrient film technique; the medium; water, gravel, sand, sawdust, rockwood, and other soilless cultures; tropical hydroponics and special applications; and plant culture. Includes photographs, drawings and tables, and resources.
Includes bibliographical references and index.
Includes bibliographical references and index.
Adult.
Adult
System requirements not stated.
Keywords: Food crops; Hydroponics